Internationalism, Democracy, Political Education: An Agenda for Foreign Language Education - Byram, Michael (2023)
In a time of renewed nationalism and challenges to democracy worsened by the COVID-19 crisis, internationalism and intercultural democratic competences are ever more important. We start with an analysis of the ideology of internationalism and its significance in times of growing nationalism and then introduce the concept ‘the plurilingual-and-interculturally competent democratically active citizen’ and the Council of Europe’s Reference Framework of Competence for Democratic Culture. The chapter continues with a project with students in Argentina and the USA. The main goal was to explore how the trauma associated with COVID-19 can become a site of ethical, political and personal self-transformation to cultivate solidarity, unity and hope. Through arts-based pedagogies and pedagogies of discomfort and intercultural citizenship, students researched artistic approaches to the pandemic in their countries, and communicated online to design artistic creations in mixed nationality groups to channel their emotions and to make a contribution to their societies responses. Evaluation of data - including students’ artistic multimodal creations, written statements about their creations - indicates that the project cultivated ‘the plurilingual-and-interculturally competent democratically active citizen’ conceptualised in the RFCDC.